2013
DOI: 10.4103/1755-6783.133703
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of HIV seropositive malaria infected pregnant women in Akure Metropolis, Southwestern Nigeria

Abstract: Background: HIV increases the risks of malaria in pregnant women, while maternal human immunode iciency virus (HIV) viral load also facilitates perinatal transmission to neonates. Malaria and HIV coinfection has been shown to exacerbate adverse pregnancy complications. Our study was designed to determine the HIV prevalence of pregnant women at an antenatal clinic in Akure in southwestern Nigeria, investigate the relationship between dual HIV and malaria infection and HIV viral load and CD4+ T cell counts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These pro-inflammatory cytokines in turn stimulate CD8+ lymphocytes, which control viremia. In our companion study carried in the same institution, the mean CD4+ T lymphocyte count decreased significantly, while HIV plasma load increased in HIV+Mal+ pregnant subjects [20]. HIV also has been shown to up-regulate adhesion molecules on endothelial cells, which may compound the adherence and sequestration seen in malaria [21].…”
Section: Discussionmentioning
confidence: 99%
“…These pro-inflammatory cytokines in turn stimulate CD8+ lymphocytes, which control viremia. In our companion study carried in the same institution, the mean CD4+ T lymphocyte count decreased significantly, while HIV plasma load increased in HIV+Mal+ pregnant subjects [20]. HIV also has been shown to up-regulate adhesion molecules on endothelial cells, which may compound the adherence and sequestration seen in malaria [21].…”
Section: Discussionmentioning
confidence: 99%
“…8 , 11 , 12 Some others reported anaemia and low CD4 count among those with malaria and HIV co-infection. 12 15 Another study reported higher viral load count. 15 However, no study has evaluated the effect of helminths alongside malaria in the HIV population of pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“… 12 15 Another study reported higher viral load count. 15 However, no study has evaluated the effect of helminths alongside malaria in the HIV population of pregnant women. This study was conducted to determine the prevalence of malaria and helminths among HIV infected pregnant women and effect on maternal CD4 counts, viral load and anemia.…”
Section: Introductionmentioning
confidence: 99%
“…HIV increases both the risk of malaria infection and the development of clinical malaria . Conversely, malaria increases HIV replication .…”
Section: Introductionmentioning
confidence: 99%
“…HIV increases both the risk of malaria infection and the development of clinical malaria . Conversely, malaria increases HIV replication . The incidence of acute malaria during an unprotected pregnancy is more than 20% and, even with currently recommended chemoprophylaxis, the incidence remains unacceptably high at 8% .…”
Section: Introductionmentioning
confidence: 99%